Identifying opportunities for collaboration in the government context: a case study in the elaboration of municipal master plans - Paula, Jonas Ribeiro; Paula, Melise (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2020: Companion Proceedings of the 16th Brazilian Symposium on Information SystemsDO - 10.5753/sbsi.2020.13127, 2020)
The objective of this article is, based on a model that proposes an approach to promote popular participation through the 3C Collaboration Model, to propose a collaborative workflow of the process of creating a municipal master plan, identifying together the opportunities for collaboration with possibility of using technologies to expand such opportunities. The Business Process Model and Notation (BPMN) will be used to map the processes and the opportunities for collaboration will be based on the 3C Collaboration Model.